2006
DOI: 10.1111/j.1478-3231.2006.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of contrast‐enhanced ultrasonography with abdominal virtual ultrasonography in assessing therapeutic response in hepatocellular carcinoma treated with radiofrequency ablation

Abstract: CEUS with VUS is effective in assessing the therapeutic response to RFA of HCC. Moreover, the number of CECT scans required is reduced by this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…The sensitivity of CEUS is .90% for detecting adequate ablation when compared with other approaches such as three-dimensional CT scans (97%) 17 and contrast-enhanced CT (91.6%). 22 The combined results from our study showed a 91% complete ablation rate, supporting the opinion that CEUS can be a substitute of CT scans in evaluation of the RFA effectiveness for HCCs.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The sensitivity of CEUS is .90% for detecting adequate ablation when compared with other approaches such as three-dimensional CT scans (97%) 17 and contrast-enhanced CT (91.6%). 22 The combined results from our study showed a 91% complete ablation rate, supporting the opinion that CEUS can be a substitute of CT scans in evaluation of the RFA effectiveness for HCCs.…”
Section: Discussionsupporting
confidence: 72%
“…24 A sufficient safe margin can greatly decrease the local tumour recurrence rate, whereas with the ablative margin width of ,5 mm, secondary RFA should be performed to ensure complete ablation. 22 Among the included studies, only two studies 15,22 have reported the complete ablated rate based on safe margin width. The results of our study indicated that the proportion of ablative margin width ,5 mm was 53%, which might be useful for the judgment of the following treatment effect for patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After RFA, CEUS can asses therapeutic response, e.g. whether the tumour was ablated completely and whether sufficient safety margins were achieved (26). CEUS facilitates the application of percutaneous US-guided treatment by improving the localization of HCCs invisible to conventional ultrasound (27).…”
Section: Role Of Ultrasound In Hepatocellular Carcinomamentioning
confidence: 99%